ADAPTATION OF TECHNOLOGY AND USE OF INTERNATIONAL LANGUAGES IN INCREASING MSMES TOWARDS INTERNATIONALIZATION AT AIDA FURNITURE - Elfiya Yetti; Sudarmiatin Sudarmiatin; Imam Mukhlis (PENANOMICS: International Journal of Economics, 2022)
The purpose of this research is to find out how companies implement in adapting to technology and the use of international languages to increase MSMEs towards internationalization. This research was conducted at Aida Furniture, Pasuruan, East Java, Indonesia. The approach used in this study is descriptive and qualitative analysis by conducting direct interviews with company owners. In addition, direct observation of the research object was also carried out and secondary data collection, namely online document searches and literature reviews. This study obtained results indicating that the company has made adaptations in technology in its production process. The use of technology is carried out by the company in the process of painting and drying products. The obstacle faced by companies to be able to export is the use of international languages. If these obstacles can be overcome positively, then the company will generate a competitive advantage so that MSMEs can compete and lead to internationalization. Technological innovations carried out by the company will accelerate the company's competitive advantage for internationalization and export.